Analisis Anomali Iklim Dalam Hubungan Dengan Produksi Padi Sawah (Oryza sativa L .) Di Kabupaten Minahasa Utara - Rogi, Dianita; Rogi, Johannes E.X.; Runtunuwu, Semuel (Sam Ratulangi University, 2023)
This study aims to look at the relationship between rainfall and lowland rice production in North Minahasa Regency from 2010 to 2020, and this research was carried out from August to October 2021. Data collection was taken using secondary data, and presented in the form of tables and graphs. The study used polynomial regression analysis using order 6 and Microsoft Excel 2016 software. The results showed that the rainfall in 2010-2020 in North Minahasa Regency fluctuated every year. The highest rainfall occurred in 2016, namely 5,322 mm and low rainfall occurred in 2015, namely 2,730 mm, the highest lowland rice production occurred in 2020, namely 8.32 tons/ha and the lowest rice production in 2010, namely 4.89 tons/ha. Based on the results of the analysis, it was found that R2 = 0.7218, which means that the correlation value is good and rainfall has a very good effect on the growth of paddy rice plants.